'Quality End of Life Care for All' (QELCA): the national rollout of an end-of-life workforce development initiative. Issue 2 (26th March 2015) - Gillett, Karen; Bryan, Liz
Abstract : Background: Most people in the UK die in National Health Service (NHS) hospitals and it is essential that NHS employees are equipped to provide high-quality end-of-life care. Government policy encourages charities to work in partnership with the NHS and hospices have the necessary expertise to deliver education in end-of-life care. Intervention: This article describes the national rollout and evaluation of the 'Quality End of Life Care for All' (QELCA) programme funded by the NHS National End of Life Care Programme. QELCA enables health professionals from acute NHS trusts to experience hospice care and empowers them to improve end-of-life care in their own practice settings. Seventeen acute NHS trusts took part with 21 hospices local to the trusts delivering the programme. Overall, 137 acute nurses participated in the programme, which involved 5 days at the hospice followed by 6 months of action-learning sets. Outcome: Participants gave concrete examples of improvements they made to end-of-life care and the majority of those who returned postcourse questionnaires believed that QELCA had changed their practice. Additional positive outcomes included better working relationships between acute trusts and hospices, and more appropriate referrals. Discussion: Participants in QELCA progressed from passively identifying problems to actively problem solving and facilitating changes in practice. This attitudinal change has the potential to stimulate and sustain real change in end-of-life care in acute hospitals. QELCA is now being delivered to other members of the multidisciplinary team, including general practitioners.